Implementation of Fiction in Teaching Reading - Ajeng Pratiwi , Ni Komang (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
This is a conceptional article which the writer proposes a concept of implementation of teaching reading by using fiction. This is aimed to investigate how the fiction are used to materials in teaching reading. It shows that materials can be used to develop students’ reading skill. The pictures in the fiction are engaging and can help students by providing clear storyline as guidance to write story. In addition, the short story also part of fiction, it makes the students have shown their improvement such as they are able to comprehend the text well, the situation of the teaching reading process become more joyful and interesting. So, it can be concluded that the implementation of teaching reading by using fiction can improve the students’ reading skill.